(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
A concrete type with a significant porosity is pervious concrete. It is applied to concrete flat constructions so that water can travel through it.. A commercial by-product created during the manufacturing of silicon metal or silicon alloys is silica fume. It is also known that silica fume enhances the mechanical properties of concrete. The main physical impact of silica fume in concrete is that it acts as a filler. Sand fills the spaces between the particles of coarse aggregate, and cement grains fill the spaces between sand grains because of their similar sizes. This highly active pozzolan reacts more quickly than regular pozzolans in terms of the chemical reaction of silica fume due to its high surface area and high amount of amorphous silica. The use of silica fume in concrete offers both engineering and financial benefits. This study discusses the ideal silica fume content for the cost effective and sustainable manufacture of concrete based on the findings of experimental research. When used as a partial replacement for opc, silica fume is shown to work best at a level of 15% (by weight). Utilizing silica fume raises strength metrics significantly while reducing workability.